Metabolite profiling and computational analysis of alkaloids of Carica papaya L. var. California leaves ethanol extract as a drug candidate - Martina Kurnia Rohmah; A’yunil Hisbiyah; Tutiek Purwanti (Universitas Ahmad Dahlan, 2026)
Papaya (Carica papaya L.) var. California leaves are widely used as traditional medicine. Several scientific studies have demonstrated that papaya leaves possess biological and pharmacological properties, with potential to be developed into a therapeutic agent. Papaya contains major secondary metabolites from the alkaloid group, including carpaine, pseudocarpaine, emetine, and dehydrocarpaine. As a major compound, we need to know its physicochemical properties, target and receptor binding properties, and potential biological functions. This research aims to determine ADME characteristics, predict target proteins, and assess drug similarity. We identified an alkaloid compound in the ethanol extract of Carica papaya L. var. California is using LC-HRMS. We utilized the Swiss ADME Webserver to analyze ADME properties, predict protein targets, and perform drug similarity analysis. We used various references to study the biological activity and effect of alkaloids on various receptor binding. LC-HRMS showed that the Carica papaya L. var. California leaves contain ethanol extracts that contain some alkaloids, including carpaine (58.3%), pseudocarpaine (2.49%), emetine (0.12%), dehydrocarpaine II (0.07%), and dehydrocarpaine I. ADME analysis showed good oral absorption, widespread distribution, no CYP-mediated interactions, and low clearance. Target prediction studies showed that papaya leaf alkaloids have three main targets: protein kinases, G protein-coupled receptors (GPCRs), and proteases. Drug similarity studies showed that papaya leaf alkaloids share structural similarities with several drugs that play roles, including anti-inflammatories, antivirals, immunosuppressants, anticancer agents, vasodilators, modulators of the nervous and cardiovascular systems, and muscle relaxants.